Sight unseen : an exploration of conscious and unconscious vision - Goodale, Melvyn A. (Oxford University Press, 2004)
"The odyssey begins and ends with the story of a young woman (here called 'Dee') apparently blind to the shapes of things in her visual world due to a devastating brain accident. As their investigations unfolded Milner and Goodale found that Dee wasn't in fact 'form-blind' at all - she could register the shapes of objects unconsciously, though she didn't at first realize it. Taking us on a journey into the unconscious brain, the two scientists who made this discovery tell the amazing story of their work, and the surprising conclusions about the normal brain's hidden capacities they were forced to reach. Written to be accessible to students and popular science readers, this book is a fascinating illustration of how the study of a damaged brain can reveal much about the human condition."--Jacket